Linux Recipes for Oracle DBAs - Kuhn, Darl (Apress, 2012)
This book provides you with task-oriented, ready-made solutions for Oracle DBAs in a Linux environment. We cover Linux topics from the DBA’s perspective of utilizing the operating system. You don’t have to read the book cover to cover. Rather, each recipe is a how-to guide for a particular problem. This format allows you to focus on a Linux/Oracle topic and its corresponding solution.